Transformative change towards sustainability: the interaction between organisational discourses and organisational practices. Issue 3 (16th April 2017) - Narayanan, Venkateshwaran; Adams, Carol A.
Abstract : This paper adopts a case study approach to explore the complex process of organisational change towards greater social and environmental sustainability. The case study of a major global financial services organisation involved interviews and examination of company documents, and their website over the period 2000–2014. The rare longitudinal empirical evidence from different sources provides important insights to how companies are responding to increasing demands for sustainable development. Using Laughlin's [1991. Environmental disturbances and organizational transitions and transformations: some alternative models. Organization Studies, 12 (2), 209–232] pathways of change model, the study investigates the interaction between organisational discourses (i.e. its interpretive schemes) and organisational practices (i.e. design archetypes). The findings demonstrate the centrality of organisational discourses, especially those relating to accounting calculative practices, to radical change towards sustainable development. The paper also contributes to the literature on institutional logics, particularly multiple institutional logics, and how these are implicated in change processes.